Understanding the Influence of Consumers’ Perceived Value on Energy-Saving Products Purchase Intention - Luo, Biao; Li, Liru; Sun, Ying (Frontiers in Psychology, 2022)
Since rapid economic growth has led to the overuse of natural resources and environmental degradation, increasing attention has been paid to environmental problems. This study aims to explore the relationship between consumers’ perceived value, satisfaction and energy-saving products purchase intention was investigated using appraisal-emotional response-coping theory. Moreover, this study further investigates these relationships in different consumer groups. In total, 399 questionnaires were collected online and offline, and results though structural equation modeling analysis shows that functional, emotional, conditional, and green value has a positive effect on consumer satisfaction and thereby promote the intention to purchase energy-saving products. However, social value is not significant for consumer satisfaction. Perceived value influences consumer satisfaction and varies among different consumers according to the results of multigroup structural equation modeling analysis. These results have practical significance for the design and marketing of energy-saving products.